2012
DOI: 10.1194/jlr.m029041
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal DGAT1 deficiency reduces postprandial triglyceride and retinyl ester excursions by inhibiting chylomicron secretion and delaying gastric emptying

Abstract: Acyl CoA:diacylglycerol acyltransferase (DGAT) 1 catalyzes the final step of triglyceride (TG) synthesis. We show that acute administration of a DGAT1 inhibitor (DGAT1i) by oral gavage or genetic deletion of intestinal Dgat1 (intestine-Dgat1−/−) markedly reduced postprandial plasma TG and retinyl ester excursions by inhibiting chylomicron secretion in mice. Loss of DGAT1 activity did not affect the efficiency of retinol esterification, but it did reduce TG and retinoid accumulation in the small intestine. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 44 publications
5
90
0
1
Order By: Relevance
“…MGAT2 is the major contributor of MGAT activity in the intestine ( 8,12 ). MGAT activity in vitro and the ability to incorporate monoacylglycerol into triacylglycerol were signifi cantly reduced in the intestine gain induced by high-fat feeding have been reported in rodents (35)(36)(37). Whether some of the inhibitors are efficacious therapeutic agents for metabolic diseases in humans remains to be determined.…”
Section: Expression Of Hmogat2 Partially Restores Metabolic Effi Cienmentioning
confidence: 99%
See 1 more Smart Citation
“…MGAT2 is the major contributor of MGAT activity in the intestine ( 8,12 ). MGAT activity in vitro and the ability to incorporate monoacylglycerol into triacylglycerol were signifi cantly reduced in the intestine gain induced by high-fat feeding have been reported in rodents (35)(36)(37). Whether some of the inhibitors are efficacious therapeutic agents for metabolic diseases in humans remains to be determined.…”
Section: Expression Of Hmogat2 Partially Restores Metabolic Effi Cienmentioning
confidence: 99%
“…Glucosyl units released in both groups were measured using a colorimetric glucose kit (Wako Diagnostics). The nonhydrolyzed group represented the free glucose measurement, while the difference between the hydrolyzed by guest, on May 9, 2018 www.jlr.org activity, such as acyl CoA:diacylglycerol acyltransferase (DGAT)1 ( 26 ), which are highly expressed in the intestine. In contrast, M2…”
Section: Biochemical Assaysmentioning
confidence: 99%
“…However, whether cholesterol concentrations and cholesterol metabolism per se are altered upon intestinal or systemic DGAT1 deficiency have not been explored. In the current study, we found that secretion of post-prandial [8]. DGAT1 possesses acyl-CoA:retinol acyltransferase activity [28], which could partly explain the reduction in chylomicron retinyl ester excursion due to intestinal DGAT1 deficiency.…”
Section: Discussionmentioning
confidence: 78%
“…Chylomicron secretion rate using [9, H(N)]triolein (Perkin Elmer, Boston, MA) and [ 14 C]cholesterol (ARC Inc., St. Louis, MO) was assessed as previously described [8] with minor modifications. Briefly, mice fed HF/HCD for 12 weeks were fasted for 4 h starting at 6 a.m.…”
Section: Chylomicron Secretionmentioning
confidence: 99%
“…Repeated administration of JTT-553 showed decreases of the liver and fat weights, and the liver TG content. The DGAT1 inhibitor was considered to suppress food consumption via the elevation of levels of gut hormones, such as GLP-1, in plasma [99]. Furthermore, JTT-553 was administrated to DIO mice and antiobesity effects and antidiabetic effects were investigated at the same time [98].…”
Section: Acyl-coa: Diacylglycerol Acyltransferase 1 Inhibitormentioning
confidence: 99%